Avaliação do programa escola ativa como política pública para escolas do campo com turmas multisseriadas: a experiência em jardim do seridó/rn (1998-2009) - Azevedo, Márcio Adriano de (2010)
This work aims at developing an evaluation of the implementation of the Program Escola Ativa as a public policy for rural schools with combined grade classrooms in Jardim do Seridó RN (1998 2009) focusing on the following dimensions: school s physical environment, training, follow up, and didactic usage of the methodology. In order to develop this research we refer to the literature that analyzes the cycle of policies (FREY, 2000). In this approach, evaluation represents an important step in the process of analyzing the implementation of public policies, as a way of measuring up their performance, as well as a guide for realignments and redefinitions (PRESSMAN; WILDAVSKY, 1998). In order to accomplish this function, the evaluator of policies must be acquainted with scientific concepts and methods that consist of describing, interpreting and analyzing the policies in the governmental sphere (MENY; THOENIG, 1992; LIMA JÚNIOR, 1978). In this perspective, we intend to investigate whether in its proposition of minimizing the blanks in the Brazilian educational system, the implementation of the Program would be contributing to the improvement of the political-pedagogical practices in the rural schools with combined grade classrooms in Jardim do Seridó RN. In order to do this research, we have developed a theoretical-methodological matrix made of analysis dimensions, variables, indicators and instruments, such as literary revision, documental analysis, semi-structured interviews with four teachers and three supervisors that work and/or have worked in Escola Ativa in that town in the period comprised among 1998 2009, besides notes taken from field observation and photographs from four rural schools with combined grade classrooms. With this research we have identified that the Program, at a national level, has gone through different phases in its implementation process, for the town was not ready to fully take the responsibilities of the autonomous expansion, in 2002. From that period on, the execution of Escola Ativa has suffered several discontinuities, such as the lack of professional training and supervising. It is also noted that the methodology contributes to the dynamization of the didactic-pedagogical activities and promotes the cooperation and autonomy of the students in the organization and the applicability of the components of the curriculum, especially of Governo Estudantil and Cantinhos de Aprendizagem. Although the directions of the Program (BRASIL, 2005) point out that Escola Ativa has among its principles social transformation, we identified that, isolated, the initiative is not capable of promoting the changes that the rural schools need, namely investments in the physical, material, pedagogical and technological infra-structure, besides the estimation and a career plan for the teachers. In a general draft of the results of this research, we realized that some aspects presented about the peculiarities of Escola Ativa in Jardim do Seridó as a governmental Program, reinforce the need for the public policies to be evaluated, in order to confront critic and operationally the planning with the practice, revising action, whenever necessary